Internet addiction: coping styles, expectancies, and treatment implications - Brand, Matthias; Laier, Christian; Young, Kimberly S. (Frontiers in Psychology, 2014)
Internet addiction has become a serious mental health condition in many countries. To better understand the clinical implications of Internet addiction, this study tested statistically a new theoretical model illustrating underlying cognitive mechanisms contributing to development and maintenance of the disorder. The model differentiates between a generalized Internet addiction (GIA) and specific forms. This study tested the model on GIA on a population of general Internet users. The findings from 1019 users showed that the hypothesized structural equation model explained 63.5% of the variance of GIA symptoms, as measured by the short version of the Internet Addiction Test (s-IAT). Using psychological and personality testing, the results show that a person’s specific cognitions (poor coping and cognitive expectations) increased the risk for generalized Internet addiction. These two factors mediated the symptoms of GIA if other risk factors were present such as depression, social anxiety, low self-esteem, low self-efficacy, and high stress vulnerability to name a few areas that were measured in the study. The model shows that individuals with high coping skills and no expectancies that the Internet can be used to increase positive or reduce negative mood are less likely to engage in problematic Internet use, even when other personality or psychological vulnerabilities are present. The implications for treatment include a clear cognitive component to the development of generalized Internet addiction and the need to assess a patient’s coping style and cognitions and improve faulty thinking to reduce symptoms and engage in recovery.